Bioinformatics Analysis of Candidate Genes Related to Fat Deposition in Yaks at Different Energy Levels - Boxuan Yang; Xiaolin Luo; Xiangfei Zhang; Tianwu An; Qin Bai; Quan Sha; Hongwen Zhao (Current Issues in Molecular Biology)
Fat deposition is important for the growth and reproduction of yaks. To investigate the differentially expressed genes in muscle tissue and fat deposition in yaks at varying energy levels, 12 healthy adult yaks with similar body conditions were selected as research subjects. They were slaughtered after being reared at the following three different energy levels: low (L), medium (M), and high (H). The most extensive dorsal muscles were collected and screened for fat metabolism-related genes using Illumina for transcriptome sequencing. The results of transcriptome analysis showed that a total of 1430 differentially expressed genes were identified across the three groups of samples. Among these, 281 differentially expressed genes were identified between the high-energy group and the low-energy group; 365 differentially expressed genes were identified between the low-energy group and the medium-energy group; and 784 differentially expressed genes were identified between the medium-energy group and the high-energy group. GO and KEGG annotations indicated that across the three different energy levels the main enriched genes were found in the adipose cytokine signaling pathways, including, AMPK, the MAPK signaling pathway, and the PI3K-Akt signaling pathway. Both up- and down-regulation of FGF-10 and NR4A1 expression were found in fat deposition-related candidate genes; the seven up-regulated genes were FGF-10, ACACB, DUSP1, c-FOS, NR4A1, RGS2, and FOXO1, and the ten down-regulated genes were LDLR, IRS2, FGF (FGF-10), TRAF2, NR4A1, HSPB1, SGK1, MYL3, LEPR, and SLC2A1. Two of the most common fat deposition genes, FASN and PDK4, were selected for q-PCR validation, along with ten candidate genes obtained from the transcriptome screening. The results showed that the expression trends of 12 genes in the three different energy level groups were consistent with those from transcriptome sequencing. This study revealed the complex transcriptome profiles of fat deposition in the muscle tissues of yaks at varying energy feeding levels and uncovered candidate genes involved in fat deposition.